The Interrelationship between Military Expenditure and External Debt: Patterns of Causation in Northern Africa Countries - Georgantopoulos, Andreas G. (Journal of Economics and Behavioral Studies, 2011)
It is supported by academics and scholars that defense expenditure can significantly affect a country’s economic growth and in some cases it influences external debt having implications in various macroeconomic indicators. However, relevant empirical studies have produced contradictory evidence while the literature in this field remains relatively poor. In this spirit, this survey investigates the causal links between military expenditure and external debt for four emerging Northern Africa countries (i.e. Egypt, Tunisia, Algeria and Morocco) during the period 1988-2009. Empirical findings on the long-term relationship between the tested variables are based on cointegration test. The Granger Causality test results using Vector Auto Regression (VAR) estimates and the Error Correction Model imply that there is no dynamic causal link between military expenditure and external debt for Tunisia, Algeria and Morocco. On the other hand regarding Egypt, results imply that a strong unidirectional causality exists running from defense expenditure to external debt. Collectively, empirical calculations show that military burden do not have any significant impact on most Northern Africa countries. The only exception is the case of Egypt; empirical results show that military expenditure robustly affect the country’s external debt. These are the only findings provided from this study that validate the hypothesis that military burden may be important in determining the evolution of debt in developing countries.